Wrist Coordination in a Kinematically Redundant Stabilization Task - Masia, L.; Squeri, V.; Burdet, E.; Sandini, G.; Morasso, P. (IEEE transactions on haptics, 2012)
We investigated how the control of a compliant object is realized by the redundancy of wrist anatomy. Subjects had to balance a one degree-of-freedom inverted pendulum using elastic linkages controlled by wrist flexion/extension (FE) and forearm pronation/supination (PS). Haptic feedback of the interaction forces between the pendulum and the wrist was provided by a robotic interface. By tuning the mechanical properties of the virtual pendulum and the stiffness of the elastic linkages it was possible to study various dynamical regimes of the simulated object. Twenty subjects (divided in two groups) were tested in four days performing the same task but with different presentation order. The stabilization strategy adopted by the subjects was characterized by primarily using the PS DoF when the pendulum was linked to stiff springs and characterized by a relatively fast dynamic response; in contrast, the stabilization task was shared by both DoFs in case of lower spring stiffness and slower dynamics of the virtual object.